2022
DOI: 10.3389/fimmu.2022.853894
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneally Delivered Mesenchymal Stem Cells Alleviate Experimental Colitis Through THBS1-Mediated Induction of IL-10-Competent Regulatory B Cells

Abstract: Mesenchymal stem cells (MSCs) show promising therapeutic potential in treating inflammatory bowel disease (IBD), and intraperitoneal delivery of MSCs have become a more effective route for IBD treatment. However, the underlying mechanisms are still poorly understood. Here, we found that intraperitoneally delivered MSCs significantly alleviated experimental colitis. Depletion of peritoneal B cells, but not macrophages, clearly impaired the therapeutic effects of MSCs. Intraperitoneally delivered MSCs improved I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Treatment improved OS rate, attenuated symptoms and ameliorated macroscopic and histologic scores in experimental mice [116]. Further analysis demonstrated that MSCs-secreted thrombospondin-1 (THBS1) may boost IL-10 + Bregs and control the development and recurrence of colitis [118]. These results confer the pivotal role of Tregs, rDC, and also Bregs in adjusting IBD progress and clarify its importance for further investigations to provide a new therapeutic avenue.…”
Section: Naive Mscsmentioning
confidence: 82%
“…Treatment improved OS rate, attenuated symptoms and ameliorated macroscopic and histologic scores in experimental mice [116]. Further analysis demonstrated that MSCs-secreted thrombospondin-1 (THBS1) may boost IL-10 + Bregs and control the development and recurrence of colitis [118]. These results confer the pivotal role of Tregs, rDC, and also Bregs in adjusting IBD progress and clarify its importance for further investigations to provide a new therapeutic avenue.…”
Section: Naive Mscsmentioning
confidence: 82%
“…In addition, is has been previously shown that i.p. delivered MSCs can alleviate the symptoms of experimental colitis in mice through induction of regulatory B Cells 50 . Although this mechanism is unlikely to be involved in our immune‐deficient mouse model, it underlines the fact that multiple mechanisms may be involved in the immune modulating and regenerative effects of MSCs.…”
Section: Discussionmentioning
confidence: 88%
“…delivered MSCs can alleviate the symptoms of experimental colitis in mice through induction of regulatory B Cells. 50 Although this mechanism is unlikely to be involved in our immune‐deficient mouse model, it underlines the fact that multiple mechanisms may be involved in the immune modulating and regenerative effects of MSCs. In fact, is has been shown that MSCs injected into the peritoneal space spread mostly to abdominal organs, including liver, spleen, and intestine, in contrast to intravenously injected cells, which have a preference for liver and lung tissue within the first 24 h after injection.…”
Section: Discussionmentioning
confidence: 91%
“…All experimental groups for colitis were induced with 3% DSS (36-50 kDa; 60316ES60, YEASEN) supplemented in the drinking water for 7 days and then received normal water for the following 3 days. For treatment, ERCs or CD73 -/- ERCs (5 th -7 th generation) were suspended in phosphate buffered saline (PBS) and injected intraperitoneally experimental mice (1×10 6 cells per mice) on days 2, 5, and 8 according to the protocols ( 31 , 32 ). All other treatments were also administered with the volume of PBS (200μL) as the vehicle group simultaneously.…”
Section: Methodsmentioning
confidence: 99%